2011
DOI: 10.1177/1469787411402437
|View full text |Cite
|
Sign up to set email alerts
|

Shall we dance? The importance of staff-student relationships to undergraduate dissertation preparation

Abstract: This article evaluates the factors that comprise the staff-student relationship as it relates to undergraduate dissertation preparation. By utilizing secondary and primary material the article pinpoints the emotionally charged backdrop to the dissertation-for both students and staff. The research points to the combined intellectual and counselling dimensions of the relationship. Data were generated through completed questionnaires by students either leading up to or finishing dissertations, by staff involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 15 publications
3
31
0
16
Order By: Relevance
“…The current research, in line with previous research (Derounian, 2011), suggests the crucial role that university teachers play in helping students to take a disciplinary lens to their research.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The current research, in line with previous research (Derounian, 2011), suggests the crucial role that university teachers play in helping students to take a disciplinary lens to their research.…”
Section: Discussionsupporting
confidence: 84%
“…This struggle is also reflected in the literature on students' engagement with research methods more generally (Murtonen and Lehtinen 2005;Wagner et al 2011;Earley 2014) and on how students use evidence in their academic work (Head 2013;Head and Eisenberg 2010). The literature also highlights the crucial role of the supervisor in the dissertation process (Derounian 2011;de Kleijn et al 2012de Kleijn et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Derounian (2011: 97) found that for undergraduates the most valued qualities of a good supervisor in rank order were: Largely concurring with Derounian (2011), Jamieson and Gray (2006) They found that generally supervisors gave high priority to the same qualities as undergraduates.…”
Section: Supervisors' Qualitiesmentioning
confidence: 90%
“…It is therefore not surprising that both pastoral and technical elements of the supervisory relationship contribute to producing a dissertation (Derounian, 2011). …”
Section: Relationshipsmentioning
confidence: 99%
“…Por otro lado, destacan la importancia de una buena relación con su director, así como la calidad y la frecuencia del feedback que reciben (Todd et al, 2004;Harrison & Whalley, 2006, 2008Heinze & Heinze, 2009;Derounian, 2011). Finalmente, las ayudas entre iguales mediante grupos, tutorías o revisiones de texto colaborativas también han demostrado ser una herramienta eficaz para facilitar el acompañamiento de los estudiantes a lo largo de su proceso de escritura y de investigación (DiPardo & Freedman, 1988;Heylings & Tariq, 2001;Inman & Silverstein, 2003;Orsmond, Merry & Reiling, 2004;Vargas Franco, 2005;Castelló, Iñesta, Pardo, Liesa & Martínez-Fernández, 2012;Corcelles, Cano, Bañales & Vega, 2013).…”
Section: Marco Teóricounclassified